2019
DOI: 10.1186/s40425-019-0558-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating in vivo efficacy – toxicity profile of TEG001 in humanized mice xenografts against primary human AML disease and healthy hematopoietic cells

Abstract: Backgroundγ9δ2T cells, which express Vγ9 and Vδ2 chains of the T cell receptor (TCR), mediate cancer immune surveillance by sensing early metabolic changes in malignant leukemic blast and not their healthy hematopoietic stem counterparts via the γ9δ2TCR targeting joined conformational and spatial changes of CD277 at the cell membrane (CD277J). This concept led to the development of next generation CAR-T cells, so-called TEGs: αβT cells Engineered to express a defined γδTCR. The high affinity γ9δ2TCR clone 5 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…These models partially overcome the absence of the natural ligand CD277J in mice 3,7,33 and allowed the initiation of a first‐in‐men study (NTR6541) 18,19,34 . With TEG011, we could utilize transgenic mice expressing human HLA‐A*24:02, 25 allowing thereby more extensive toxicity studies of TEG011 in different tissues as compared to TEG001 26,32 . Although we did not investigate all organs, and despite the fact that TEG011 did not persist until day 72 in the peripheral blood of all mice, we provide strong evidence that TEG011 does not induce toxicity against human HLA‐A*24:02 expressing nontumor healthy tissues.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These models partially overcome the absence of the natural ligand CD277J in mice 3,7,33 and allowed the initiation of a first‐in‐men study (NTR6541) 18,19,34 . With TEG011, we could utilize transgenic mice expressing human HLA‐A*24:02, 25 allowing thereby more extensive toxicity studies of TEG011 in different tissues as compared to TEG001 26,32 . Although we did not investigate all organs, and despite the fact that TEG011 did not persist until day 72 in the peripheral blood of all mice, we provide strong evidence that TEG011 does not induce toxicity against human HLA‐A*24:02 expressing nontumor healthy tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Toxicity studies of compounds targeting metabolic changes remain a major challenge as such changes cannot be readily studied in detail in all organs 3 . Therefore, we proposed efficacy‐toxicity models for TEGs targeting joint spatial and conformational changes in CD277 (later referred as CD277J) 3 through a γ9δ2TCR (TEG001) by co‐incubating TEG001 with healthy and diseased tissues in an artificial 3D bone marrow niche 32 or in a mouse model where either healthy cord blood‐derived CD34 + progenitor or primary leukemia cells were engrafted 26 . These models partially overcome the absence of the natural ligand CD277J in mice 3,7,33 and allowed the initiation of a first‐in‐men study (NTR6541) 18,19,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of cell populations is compounded in studies combining multiple types of implanted human cells, as is often done for immunotherapy. 21,23,86 Such studies have been conducted in NSG mice, including the use of anti-PD1 74,93 and CAR-T 2,47 cell therapy. These studies have shown humanized mice to be a superior model in testing immunotherapies, and it is likely that similar studies in NSG-SGM3 mice are currently being conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Human acute myeloid leukemia (AML) animal models can be obtained via AML blasts and cord blood-derived human progenitor cell engraftment into NSG mice. The results are visible after 6-8 weeks, and various CAR T-cell therapies can be tested [220].…”
Section: Humanized Mice Modelsmentioning
confidence: 99%